Analisis Model Mental Peserta Didik SMA dalam Memahami Konsep Laju Reaksi - Priska Yohanita Sodanango; Munzil Munzil; Sumari Sumari (Graduate School of Universitas Negeri Malang, 2021)
Abstract: Reaction rate is concept that involves abstract concepts, chemical phenomena, mathematical operations, and practical activities. The characteristics of it require students to have the ability to think scientifically, understand chemical representations, and have good mathematical and practical skills. Based on several research studies, most of the students missed these four abilities, so the concept of reaction rate is considered difficult and affects students' mental models. It is necessary to analyse students' mental models to see the description of students' mental models in understanding chemical concepts. The purpose of this research was to specify the kind and relationships of student’s mental models in understanding the concept of reaction rate.Abstract: Teori laju reaksi melibatkan konsep abstrak, fenomena kimia, operasi matematik, dan praktikum. Karakteristik konsep mengharuskan peserta didik untuk memiliki penguasaan bernalar ilmiah, memahami representasi kimia, keterampilan aritmetika dan praktikum secara benar. Beberapa studi penelitian mencatat, keempat kemampuan ini belum dikuasai oleh peserta didik, sehingga konsep laju reaksi dianggap sukar dan mempengaruhi model mental peserta didik. Perlu dilakukan analisis model mental peserta didik untuk melihat gambaran model mental peserta didik dalam menguasai konsep kimia. Tujuan penelitian ini adalah untuk mengetahui ragam dan hubungan model mental peserta didik dalam memahami konsep laju reaksi.